Myofascial release in myofascial pain in elderly patients with lung cancer under palliative care: An integrative review (Research, Society and Development, 2023)
Myofascial release is considered a promising therapy for pain relief in various clinical populations. However, its application and effectiveness in elderly patients with palliative care for lung cancer are underexplored topics in the scientific literature. The aim of this study was to investigate the role of myofascial release in myofascial pain in elderly patients with lung cancer under palliative care. This study is an integrative review that included studies from 2017 to 2022, with a search strategy combining the following descriptors: Myofascial release therapy; Myofascial pain syndrome; Elderly; Lung neoplasms; and Palliative care, in the following databases: BVS, Scielo, PubMed, Lilacs, and PEDro. Nine articles that met the study's objectives were included. Myofascial release demonstrated positive effects in relieving muscle tension, improving circulation, comfort, mobility, pain relief, sleep quality, depressive and anxious symptoms, functionality, and quality of life. The approach should consider not only physical symptoms but also emotional and psychological aspects associated with pain, especially in lung cancer patients receiving palliative care. Rigorous clinical trials are recommended to comprehensively assess the efficacy and safety of myofascial release in this population, with the aim of improving the care provided to them.